Pengungkapan Manajemen Risiko: Ukuran Dewan Komisaris Independen, Struktur Kepemilikan, dan Keberagaman Gender Dewan Komisaris dengan Ukuran Perusahaan sebagai Variabel Kontrol - Muhamad Muslih; Defina Damayanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Transparent presentation of information related to the process of identifying, evaluating, and controlling risks. This study aims to evaluate the impact of the independent board of commissioners, company ownership structure, and gender diversity on the level of risk management disclosure. This study focuses on transportation and logistics companies listed on the Indonesia Stock Exchange during the 2019-2023 period. Risk management disclosures were conducted using ISO 31000:2018. The study employed quantitative methods with secondary data and panel data regression analysis using Eviews-12. The sample consisted of 95 companies selected by purposive sampling. Based on the results of the simultaneous analysis, all independent variables showed a significant influence on the level of risk management disclosure. Based on partial analysis conducted by controlling for certain variables, it was found that the independent board of commissioners and the level of gender diversity on the board had a positive influence on the level of risk management disclosure. Conversely, institutional ownership and managerial ownership aspects showed a negative influence on risk management disclosure practices. In addition, the analysis results showed that the level of public ownership did not have a significant influence on risk management disclosure.